A comparison of isocapnic buffering phase of cross-country skiers and alpine skiers - Eryılmaz S. Korkmaz; M. Polat (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Purpose: The purpose of this study was to compare the isocapnic buffering phase in cross-country skiers and alpine skiers during an incremental treadmill exercise test. Material: International level male junior skiers including twelve cross-country skiers and ten alpine skiers took part in the study. All participants performed an incremental treadmill exercise test to determine ventilatory threshold (VT), respiratory compensation point (RCP), and maximal oxygen uptake (VO2max). The isocapnic buffering phase was calculated as the difference in VO2 (ICBVO2) and running speed (ICBSPEED) between RCP and VT and expressed in either absolute or relative values. Results: VO2max, maximal running speed, time to exhaustion, both absolute and relative VT values and absolute RCP values were higher in the cross-country skiers than in the alpine skiers (P<0.05), whereas relative RCP showed similar values in both group (p > 0.05). Absolute ICBVO2 and ICBSPEED showed similar values in both group (p > 0.05), whereas relative ICBVO2 and ICBSPEED were found to be significantly higher in alpine skiers than in cross-country skiers (P < 0.05). Maximal respiratory exchange ratio was higher in alpine skiers than in cross-country skiers. Conclusions: The current findings suggest that anaerobic training may induces specific metabolic adaptations leading to increase in buffering capacity which may be a contributing factor to continue to exercise for relatively longer periods of time above the VT. Longer ICB phase in the anaerobic-trained athletes may an important factor in relation to the enhance high-intensity exercise tolerance.